eIF2-dependent and eIF2-independent modes of initiation on the CSFV IRES: a common role of domain II - Pestova, Tatyana V (Nature Publishing Group, 2008)
Specific interactions of the classical swine fever virus internal ribosomal entry site (IRES) with 40S ribosomal subunits and eukaryotic translation initiation factor (eIF)3 enable 43S preinitiation complexes containing eIF3 and eIF2–GTP–Met-tRNA(Met)(i) to bind directly to the initiation codon, yielding 48S initiation complexes. We report that eIF5B or eIF5B/eIF3 also promote Met-tRNA(Met)(i) binding to IRES–40S complexes, forming 48S complexes that can assemble elongation-competent ribosomes. Although 48S complexes assembled both by eIF2/eIF3- and eIF5B/eIF3-mediated Met-tRNA(Met)(i) recruitment were destabilized by eIF1, dissociation of 48S complexes formed with eIF2 could be out-competed by efficient subunit joining. Deletion of IRES domain II, which is responsible for conformational changes induced in 40S subunits by IRES binding, eliminated the sensitivity of 48S complexes assembled by eIF2/eIF3- and eIF5B/eIF3-mediated mechanisms to eIF1-induced destabilization. However, 48S complexes formed by the eIF5B/eIF3-mediated mechanism on the truncated IRES could not undergo efficient subunit joining, as reported previously for analogous complexes assembled with eIF2, indicating that domain II is essential for general conformational changes in 48S complexes, irrespective of how they were assembled, that are required for eIF5-induced hydrolysis of eIF2-bound GTP and/or subunit joining.